Demonstration of self-healing barrier films for vacuum insulation panels. (June 2019) - Biswas, Kaushik; Gilmer, Dustin; Ghezawi, Natasha; Cao, Peng-Fei; Saito, Tomonori
Abstract: This article presents the demonstration of a rapid self-healing system for barrier films of vacuum insulation panels (VIPs). The proposed self-healing films can improve the durability of VIPs by in-situ remediation of film defects. The self-healing concept has seen limited applications in buildings, and the current work is the first proposed application to VIPs. VIPs can achieve an order-of-magnitude lower thermal conductivity than traditional foam and fibrous building insulations. The key to the ultra-low thermal conductivity of VIPs is an evacuated core that is fully-encapsulated within impermeable barrier films. Evacuation of the core eliminates the gas conductivity, which is the dominant contributor to heat transfer in traditional insulation materials. Thus, the integrity of the VIP barrier films is critical. The proposed self-healing system can seal accidental cuts and punctures to the barrier films to maintain their impermeability and, hence, the low conductivity of VIPs. Here, the proof-of-principle of a two-part chemical reaction-based self-healing system is presented, including the evaluations of reaction kinetics using chemical-structure analysis and time-dependent viscosity change, and demonstration of self-healing performance via puncture tests in a vacuum pump apparatus. Multiple chemical combinations of epoxies and curing agents were investigated with respect to reaction kinetics and chemical stability. Epon 8111 as an epoxy and poly(ethyelenimine) (PEI) as a curing agent were identified as the optimum chemicals with a curing time of 22 s as evaluated by an agitating stirrer experiment. 1 H nuclear magnetic resonance (NMR) spectra analysis identified the curing reaction occurring mainly via the Michael amine-acrylate addition. The measured time-dependent viscosity change of diluted Epon 8111 and PEI solutions agreed well with a gelation model of typical epoxy curing kinetics, which predicted a very fast reaction rate for the undiluted chemicals. Finally, puncture tests of small-scale film specimens containing Epon 8111 and PEI in a vacuum pump system demonstrated that the self-healing reaction happens very rapidly and the healed films maintain the system vacuum. Highlights: Evaluated self-healing chemistries for barrier films of vacuum insulation panels. Studied reaction kinetics to select appropriate self-healing chemistry. Performed experiments to evaluate efficacy of self-healing chemistry. Demonstrated self-healing prototype films that can seal punctures and maintain the film impermeability.